2021
DOI: 10.1039/d1tc00062d
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the nonlinear absorption of fluorescent dyes by substitution at a boron center

Abstract: The tuning of the spectroscopic signatures of boron-carrying fluorescent dyes by subtle chemical modifications is achieved. In more details, we propose a new series of compounds incorporating up to three...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The synthesis of D was carried out in a similar way to dyes presented in a previous publication by some of the present authors. 39 The procedure is described in the Methods and Protocols , but we want to emphasize that unlike in other studies aiming at characterizing XB interactions in solutions based on absorption and emission, we used a non-competitive environment without any additional solvent. Furthermore, all spectra reported here were recorded in solvents freshly distilled under a nitrogen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of D was carried out in a similar way to dyes presented in a previous publication by some of the present authors. 39 The procedure is described in the Methods and Protocols , but we want to emphasize that unlike in other studies aiming at characterizing XB interactions in solutions based on absorption and emission, we used a non-competitive environment without any additional solvent. Furthermore, all spectra reported here were recorded in solvents freshly distilled under a nitrogen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the presence of BF 2 ‐group also increases significantly 2PA cross‐section as demonstrated by comparisons between BF 2 ‐dyes and its precursor [51] . Moreover, the 2PA properties of BF 2 ‐containing dyes can be tuned by various synthetic strategies [52,53] . For the purpose of the present study we designed three different series of dyes ( A , B , and C see Figure 1) containing the difluoroborate electron‐withdrawing moiety.…”
Section: Introductionmentioning
confidence: 94%
“…[51] Moreover, the 2PA properties of BF 2 -containing dyes can be tuned by various synthetic strategies. [52,53] For the purpose of the present study we designed three different series of dyes (A, B, and C see Figure 1) containing the difluoroborate electronwithdrawing moiety. Previously, some of us showed that structure similar to series A might yield quite large s 2PA .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations